Wybrane problemy upadku Tyrnowa - Marinow, Kirił (Acta Universitatis Lodziensis. Folia Historica, 2005)
This article is devoted to a few aspects of Timovo’s fall, in the year 1393. These problems in the author’s opinion have not lived to witness a satisfactory solution until now. In the first part of the article the author rejected an opinion, according to which patriarch Euthymius was the commander of the Bulgarian capital’s defence. In the second part he answered the question, who, from the ottoman side, commanded the siege of Tamovo? The analysis of the sources leads to conclusion, that Bayezid I, the then ottoman ruler, was at the head of the Turkish army, by the walls of the town. In the third part author expresses criticism of J. Andreev’s theses, concerning the reasons for the offence and circumstances, in which Turkish expedition against Tamovo came into effect. He formulates the thesis according to which the purpose of this expedition was to subjugate John SiSman and to prevent him from joining the coalition, which had been created by Zigmond of Luxembourg. In the fourth part the author confronts different information from the sources and different views of the scholars, concerning the number of the ottoman army, which besieged the town. Next, he arrives at a conclusion, that, there were probably around 30-40 thousands warriors. In the fifth part he refers to a question of a possible participation of the Vidin’s tsar, John Sracimir, and the ruler of Velbuzd, Konstantin Dragas, in the ottoman expedition against Tirnovo. The sources don’t allow to determine this issue unambiguously, although it’s possible, that the armies of these rulers didn’t take participation in the siege. The last part of this article refers to the problem of a possible relief for Tfimovo, organized by John Sisman. Author draws a conclusion, that contemporaneously existing sources don’t allow to produce a thesis, in light of which the Bulgarian tsar really organized a military help for his capital, during the ottoman siege.